Ethanol is inefficient to remove endodontic sealer residues of dentinal surface - Victorino, Keli Regina [UNESP; Campos, Edson Alves de [UNESP; Só, Marcus Vinicius Reis [UNESP; Kuga, Milton Carlos [UNESP]; Faria Júnior, Norberto Batista [UNESP; Keine, Katia Cristina [UNESP; Alvarenga, Fábio Augusto de Santis [UNESP (My University, 2013)
Endodontic sealer residues on dentinal surface have negative effects on adhesion of adhesives system and/or can cause discoloration of the dental crown. Objective: To evaluate the efficacy of 95% ethanol in removal of residues of epoxy-based (AH Plus), methacrylate-based (Epiphany SE) or calcium-based (Sealapex) sealers on dentinal surface. Material and methods: Thirty-two bovine incisor dental crown fragments (0.5 mm x 0.5 mm) were treated with 17% EDTA and 2.5% NaOCl. The specimens were divided into three experimental groups (n = 10): G1 (AH Plus), G2 (Epiphany SE) and G3 (Sealapex). In each group was applied a coating of one endodontic sealer type and were left undisturbed for 5 minutes. After this period, the specimens were cleaned with 95% ethanol. The control group was composed by two specimens that did not receive any sealer or cleaning treatment. The sealer residues persistence after cleaning with 95% ethanol was evaluated by scanning electron microscopy (x500) and a score system was applied. Data obtained were analyzed by Kruskal-Wallis and Dunn tests (α = 5%). Results: Moderate amount of endodontic sealer residues were observed in all groups, regardless of the endodontic sealer compositions. G1, G2 and G3 presented similar amount of sealer residues on dentinal surface after cleaning with 95% ethanol (p > 0.05). Conclusion: 95% ethanol was inefficiency to remove completely AH Plus, Epiphany SE and Sealapex residues of sealer-contaminated dentin.
Keywords: Endodontics; Image analysis; SEM; Surface analysis